2019
DOI: 10.1002/jbm.b.34328
|View full text |Cite
|
Sign up to set email alerts
|

CoCr porous scaffolds manufactured via selective laser melting in orthopedics: Topographical, mechanical, and biological characterization

Abstract: Over the last decade, advances in additive manufacturing have allowed to obtain complex 3D porous lattice in materials suitable for orthopedic applications. Whereas 3D‐melted titanium alloys have been extensively investigated, little is the current knowledge on the feasibility of bone‐replicating CoCr porous scaffolds manufactured via selective laser melting (SLM). Moreover, the effect of topography on bone cells viability and proliferation has not been fully explored yet. Small cylindrical porous lattices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Advantages and disadvantages of the CoCr alloys[68,92]. Ni) alloys are metals made from a combination of nickel as the primary element and another material such as Ni-Al alloy, Ni-Cr alloy or Ni-Ti alloy.…”
mentioning
confidence: 99%
“…Advantages and disadvantages of the CoCr alloys[68,92]. Ni) alloys are metals made from a combination of nickel as the primary element and another material such as Ni-Al alloy, Ni-Cr alloy or Ni-Ti alloy.…”
mentioning
confidence: 99%
“…Furthermore, Leary concluded that the face-and-bodycentered geometry with vertical struts (FBCCZ) has the highest absolute values of strength and modulus [84] while the FCCZ geometry has the best specific strength and modulus compared to other samples [85]. Furthermore, the BBC geometry has been reported to have higher equivalent strength and specific strength than crossing rod unit cell [86], while crossing rod presents higher ultimate and yield strength than circular unit cell [87]. Topological optimization leads usually to cell geometries that often result in improved mechanical performances [88].…”
Section: Compression Testsmentioning
confidence: 99%
“…Muller et al [107] found that a certain level of randomization improves the mechanical properties while Raghavendra et al [108] reported regular structures having higher values of strength. Other works tested lattice structures to compare their properties with the natural bone [7,87] or to validate the related FEM simulation [120,121].…”
Section: Tensile Testmentioning
confidence: 99%
“…Imwinkelried 30 has studied the effects of porosity on mechanical properties of Ti scaffolds and concluded that 50-80% porosity of Ti scaffolds was consistent with natural bone in terms of stiffness and strength. Moreover, based on a well-designed experiment, Caravaggi et al 31 investigated the selective laser melting (SLM) complex of 3D porous lattice CoCr scaffolds such as crossing-rod, trabecular, and circular with pore sizes of approximately 510, 670, and 800 μm, respectively. The research showed favorable biocompatibility and mechanical property of the SLM porous CoCr scaffolds.…”
Section: Introductionmentioning
confidence: 99%